Spontaneous inertia-gravity wave emission from a nonlinear critical layer in the stratosphere - Polichtchouk, Inna; Scott, Richard K. (Quarterly Journal of the Royal Meteorological Society, 2021)
Using a nonlinear global primitive equation model, spontaneous inertia‐gravity wave (IGW) emission is investigated in an idealized representation of the stratospheric polar night. It is shown that IGWs are spontaneously emitted in the interior of the fluid in a jet exit region that develops around a nonlinear Rossby wave critical layer. Two key ingredients for the generation are identified: the presence of a Rossby wave guide on the polar night jet; and a zero wind line on the jet flank that gives rise to nonlinear Rossby wave breaking and strong distortion of the flow. The emission of IGWs appears here as a quasi‐steady process that begins at a well‐defined time when the flow deformation becomes large enough. Part of the emitted IGWs undergoes wave capture by the cat's‐eye flow in a Rossby wave critical layer. Another part – in the form of a well‐defined IGW packet – escapes the wave capture limit, and propagates away into the far field. The propagating wave packet is numerically well‐converged to increases in both vertical and horizontal resolution and thus provides an ideal test bed for understanding IGW emission and informing non‐orographic gravity wave drag parametrization design. Peer reviewed